2021
DOI: 10.1002/jssc.202000932
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of Danqi tablet by ultra‐performance liquid chromatography coupled with triple quadrupole mass spectrometry integrated with bioassay

Abstract: Danqi tablet composed of the dried roots of Salvia miltiorrhiza and Panax notoginseng is a well‐known Chinese patent medicine commonly used for the treatment of cardio‐cerebrovascular diseases such as coronary heart disease and myocardial ischemia. Numerous chemical constituents belonging to S. miltiorrhiza and P. notoginseng were detectable in Danqi tablet. Here, we established and validated a rapid and sensitive ultra‐performance liquid chromatography coupled with triple quadrupole mass spectrometry method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although the antithrombotic bene ts of P.notoginseng roots have been well documented before (Fu et al, 2021), few studies have evaluated the medicinal use of PNF for the prevention and treatment of cardiovascular diseases. Our previous studies showed that two saponin monomers (Rb2 and Rd2) in PNF signi cantly attenuated platelet function (Zuo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the antithrombotic bene ts of P.notoginseng roots have been well documented before (Fu et al, 2021), few studies have evaluated the medicinal use of PNF for the prevention and treatment of cardiovascular diseases. Our previous studies showed that two saponin monomers (Rb2 and Rd2) in PNF signi cantly attenuated platelet function (Zuo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As two groups of diastereoisomers, compounds 1−4 and 5−8 have the same plane structure and almost the same mass spectrum features, making their separation difficult [21, 22]. To overcome this barrier, UHPLC‐MS/MS has been used for improving sensitivity and separation efficiency, while reducing acquisition time [23, 24]. Moreover, in light of the health risks associated with PAs, the recommended daily intake of PAs has been studied recently.…”
Section: Introductionmentioning
confidence: 99%